Manipulação genética de fatores de transcrição diferencialmente expressos sob indução de expressão de enzimas heterólogas em Aspergillus nidulans : Genetic manipulation of differentially expressed transcription factors under induction of expression of heterologous enzymes in Aspergillus nidulans - Antoniel, Everton Paschoal, 1995- (2020)
Orientador: André Ricardo de Lima Damasio